The effect of Internet Financial Reporting (IFR) on firm value, stock price, and stock return in the manufacturing companies listed in Indonesia Stock Exchange - Eka Ratna Maryati (The Indonesian Accounting Review, 2014)
The rapid development of internet could be used by the company to disclose financial and non financial information quickly to the investors. However, in Indonesia the disclosure of financial and non financial information through the internet is rarely done by the company. This study aims to examine whether the use of internet financial reporting affect the firm value, stock price, and stock return in manufacturing companies listed in Indonesia Stock Exchange. The data of this study were collected from a sample of 50 manufacturing companies listed in Indonesia Stock Exchange. Simple regression analysis was employed in this study. From the process of analysis, it was found that the companies that used internet to disclose financial and non financial information have a significant and positive impact on their firmvalue and stock price.